Heavy Metals Transfer from Milk into Milk Products - Tawfik Hassan; Mohamed S. Elarnaoutti (Turkish Journal of Agriculture: Food Science and Technology)
The study aimed to calculate the percent transfer of lead (Pb), cadmium (Cd), copper (Cu), and zinc (Zn) from milk into cream, skim milk, butter, buttermilk, soft cheese, and whey manufactured in the laboratory. The four heavy metals were determined using the ICP method. The results revealed that the percentage of these metals transferred to milk products varied from 9.48 to 72.63%, with skim milk exhibiting the highest transfer rate (67 to 72.63%) and butter displaying the lowest transfer rate (9.48 to 13.94%). These findings are expected to urge the artisanal dairy industry to decide on the best way to process milk that does not comply with the maximum permissible levels of Pb, Cd, Cu, and Zn into a safe product for the consumer.